Increasing the quantity of separated post-consumer plastics for reducing combustible household waste: The case of rigid plastics in Flanders. (August 2018) - Jacobsen, R.; Willeghems, G.; Gellynck, X.; Buysse, J.
Highlights: Plastic recycling schemes have an impact on the separated amount of plastics. Easy and convenient separation options collect most plastics. Regression analysis model by applying cross-sectional data. Data were collected for all 308 municipalities in Flanders. Deeper causes for using certain separation schemes. Abstract: In Flanders, Belgium, rigid and soft plastics represent an interesting fraction of residual household waste as a potential 80 000 Gg a −1 can be recycled instead of incinerated. Removing a large amount of rigid packaging and non-packaging plastics from the residual household waste fraction could contribute to the goal to reduce the amount of residual household waste to less than 150 kg capita −1  a −1 for the Flemish region, where currently only 20% of plastics are collected selectively in drop-off facilities. Given the wide range of plastic separation schemes across the region, it is the aim of this paper to identify whether the applied separation options have an impact on the quantity of separated plastics, and, moreover, which scheme is able to separate most plastics. Cross-sectional data for the period 2008–2012 were collected for all 308 Flemish municipalities to conduct a regression analysis. The results of the analysis show that the quantity of separated plastics differs significantly between the different separation schemes used. If municipalities change their separation schemes, Flanders as a whole would be able to collect more plastic waste to better comply with its own objectives and EU regulation on recycling. Improved separation-at-source recycling initiatives, by applying the appropriate separation scheme for plastics, may increase recycling growth.